2011
DOI: 10.1111/j.1532-7795.2011.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Ego Development, Ego Strengths, and Ethnic Identity Among First Nation Adolescents

Abstract: Three conceptualizations of psychosocial development were investigated among Canadian First Nation adolescents. Loevinger's social cognitive model of ego development reflects the way in which an individual views the self and social reality. From Eriksonian theory, ego strengths refer to the emergent values or outcomes that represent resolution of the eight psychosocial stages of development, and ethnic identity is a domain of personal identity with special relevance for minorities. As expected, age and biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The majority of converssations about how AI/AN identity affects AOD use and other risk behaviors concerned how protective AI/AN identity could be and the healing properties of AI/AN practices and worldviews. This is also supported by existing studies that show protective effects of AI/AN identity on behavioral health outcomes (Gfellner & Armstrong, 2012; Tyser, Scott, Readdy, & McCrea, 2014). …”
Section: Discussionsupporting
confidence: 83%
“…The majority of converssations about how AI/AN identity affects AOD use and other risk behaviors concerned how protective AI/AN identity could be and the healing properties of AI/AN practices and worldviews. This is also supported by existing studies that show protective effects of AI/AN identity on behavioral health outcomes (Gfellner & Armstrong, 2012; Tyser, Scott, Readdy, & McCrea, 2014). …”
Section: Discussionsupporting
confidence: 83%
“…According to Erikson's theory, people experience the extremes of ego strength and weakness while resolving the crises of each developmental stage over a lifetime. [14][15][16] This theory has been supported by Johnson, Beebe, Mortimer, and Snyder, 17 who demonstrated that adolescents with well-developed ego strength at a previous stage had more positive self-esteem, lower self-derogation and depressive affect, more positive wellbeing, and more positive intrinsic and extrinsic work values than those with less-developed ego strength. Moreover, such individuals were better adapted for school than those with less-developed ego strength.…”
Section: Ego Strength In Childrenmentioning
confidence: 92%
“…Before analyzing the factor structure of the preliminary scale, I determined the degree of correlation between items by analyzing the overall correlation of each sub-factor and analyzed the internal consistency of the items. Analysis revealed that the correlation of 9 out of 55 items (11,12,13,15,22,23,24,26,55) was not statistically signi cant; thus, the nine items were removed. Afterwards, multiple factor analysis and item analysis were conducted to remove items with low factor loadings and reliability problems and that posed duplication problems in terms of content validity.…”
Section: Stage 3: Factor Analysis Of the Cessmentioning
confidence: 99%
“…Erikson [13] claimed that there are eight distinct and intrinsic ego strengths throughout one's lifetime: hope, will, purpose, competence, delity, love, care, and wisdom. According to Erikson's theory, people experience the extremes of ego strength and weakness while resolving the crises of each developmental stage over a lifetime [14,15,16]. This theory has been supported by Johnson, Beebe, Mortimer, and Snyder [17] who demonstrated that adolescents with well-developed ego strength at a previous stage had more positive self-esteem, lower self-derogation and depressive affect, more positive wellbeing, and more positive intrinsic and extrinsic work values than those with less-developed ego strength.…”
Section: Ego Strength In Childrenmentioning
confidence: 99%